Emerging athletes’ career transitions in professional sport: an existential multi-case perspective - Thomas, P. G.; Lucas, P.; Walters, S.; Oldham, A. R. H. (Frontiers in Sports and Active Living, 2024)
Introduction This article examines athletes preparing for, transitioning into, or going through the developmental stages of a professional sports career, referred to as the emerging athlete career transition. This transition includes events such as selections, Junior-to-Senior promotions, contracting, migration, and early exits. The article presents the collective findings of a multi-case study in three professional sports: rugby league, basketball, and boxing. Method Consistent with pragmatic qualitative research methodology, a stratified data set was collected and analysed, incorporating researcher-practitioner fieldwork, interviews, documents and artefacts for these cases. This article explores unique events and the demographic and cultural implications of navigating emergent transitions along professional sporting pathways in New Zealand. Findings These findings highlight the importance of building self-efficacy as a pre-condition for coping through preparation and experience. Recommendations Recommendations include fostering collaborative cultures and authentic support relationships to facilitate better coping alongside athletic and personal development in these high-pressured environments. Furthermore, understanding existential perspectives of meaning, choice, and responsibility provides insights for developing the resources that allow emerging athletes to thrive in life beyond sport.